(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
Emergency damage to a pipeline may lead to the occurrence of a fire. The nature of the flame can vary. This paper considers the case of a jet flame. The impact of a jet flame is often underestimated, since there are fairly effective methods for combating this phenomenon, and it is believed that it does not require immediate action to prevent unforeseen consequences. However, if a parallel pipeline or containers with flammable products are located nearby, a domino effect may occur, i.e., damage to the pipeline, ignition of transported products, equipment, as well as threats to human life and buildings. This work presents results obtained during an experimental study of the impact of an acoustic jet flame on a pipe containing stagnant gas or water. Using sensors, the temperature of the flame impinging on a pipe located at a fixed distance was studied. Temperature changes were examined as a function of heating time, fire intensity, and position on the pipe. After 19.5 s, an initial increase in the air temperature inside the pipe to about 20 °C was recorded; after 150 s it rose to a maximum of 600 °C, and to about 800 °C after approximately 360 s. In the second stage of the experiment, when the pipe contained water, the heating rate in the wall region in contact with the liquid was significantly lower than in the first stage of the experiment. The maximum temperature reached only about 150 °C. Based on the temperatures of the jet flame and the pipe, the heat fluxes reaching the pipe and the corresponding heat transfer coefficients were determined. The study demonstrated the necessity of investigating the effects of jet flames to ensure fire protection, in particular by providing a safe distance between pipelines. The obtained results can be applied to modeling the possibility of chain (domino) damage effects in pipeline networks.